Enacting accountability reforms in Brazil: the mediating role of school leadership (Práxis Educativa, 2023)
This article aims to analyse the role of school leaders in mediating education accountability policies in Brazil. The study is framed by a sense-making and contingent leadership framework and is guided by a ‘realist evaluation’ methodological approach. The qualitative research conducted in four schools in Belo Horizonte shows that school leaders play a substantial role in mediating how school accountability reforms are received. They enact different roles, behaviours and practices, shaped by the sense-making and perception of accountability reforms and dependent upon three main contingent factors: leaders’ positional power and gender, socio-economic school composition and schools’ administrative dependency.Keywords: School leadership. Brazil. Test-based accountability policy.